Technological Developments in Indian Scheduled Commercial Banks: A Comprehensive Analysis of Technological Developments in the Indian Banking Sector (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Information technology plays vital role in the development of any industry through reducing thegeographical barriers. Indian Banking sector has been showing greater emphases on the technology andinnovation since the reforms. The Indian banking sector has undergone noteworthy transformation fromlocal branch banking to anywhere-anytime banking with the implementation of technology. Over the pastcouple of years, a huge growth has been registered in the number of transactions done throughelectronic devices. Indian banks have increased number of technological products like Net Banking,Mobile Banking, Online Shopping, Ticket Booking, Bill Payment and Automated Teller Machines (ATMs)etc. The present study is an attempt to analyze the technological developments in Indian banking sector.